An 8-factor model for evaluating crew race performance - Cornett, J.; Bush, P.; Cummings, N. (International Journal of Sports Science and Engineering, 2008)
There are no models in the current literature that offer a unified theory of all of the factors that define crew race strategy and race day performance. This paper proposes an 8-factor model of crew race performance and summarizes the related literature. The model suggests those factors that should be used to analyze and evaluate the performance of crews in actual races.